2016
DOI: 10.3390/ijms17050658
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide and Microwave-Assisted Extraction of Functional Lipophilic Compounds from Arthrospira platensis

Abstract: Arthrospira platensis biomass was used in order to obtain functional lipophilic compounds through green extraction technologies such as supercritical carbon dioxide fluid extraction (SFE) and microwave-assisted extraction (MAE). The temperature (T) factor was evaluated for MAE, while for SFE, pressure (P), temperature (T), and co-solvent (ethanol) (CS) were evaluated. The maximum extraction yield of the obtained oleoresin was (4.07% ± 0.14%) and (4.27% ± 0.10%) for SFE and MAE, respectively. Extracts were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Several researchers have used co-solvents such as ethanol [26,108,109,111,113,114,118,120,121,122,123,124,125,126,127], acetone [113], vegetable oil [26,106,128] as polarity modifiers for the efficient recovery of carotenoids such as β-carotene [113,118], astaxanthin [106,109,114,120,121,122,125,129], lutein [111,113] and zeaxanthin [118]. Since supercritical CO 2 is non-polar, addition of a small amount of co-solvent increases the ability of supercritical CO 2 to dissolve relatively polar carotenoids.…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have used co-solvents such as ethanol [26,108,109,111,113,114,118,120,121,122,123,124,125,126,127], acetone [113], vegetable oil [26,106,128] as polarity modifiers for the efficient recovery of carotenoids such as β-carotene [113,118], astaxanthin [106,109,114,120,121,122,125,129], lutein [111,113] and zeaxanthin [118]. Since supercritical CO 2 is non-polar, addition of a small amount of co-solvent increases the ability of supercritical CO 2 to dissolve relatively polar carotenoids.…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…Recently, Esquivel-Hernández et al [126] showed that MAE is an excellent technique for the recovery of total carotenoids from microalgae/cyanobacteria Arthrospira platensis (Spirulina). MAE extraction performed using a mixture of methanol/ethyl acetate/light petroleum (1:1:1 v / v ) at 400 W power, 50 °C temperature and 1 bar pressure, for 15 min yielded 629 μg/g of total carotenoids, which was significantly higher than the yield obtained by SFE (283 μg/g) (ref).…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…When the cosolvent is used at 53.33% of CO 2 ratio, the highest amount of extracts was obtained. In case of MAE extraction, the most efficient experimental condition was obtained at 400 W and 50 C [21].…”
Section: Applications Of Mae As a Green Extraction Technique In Food mentioning
confidence: 99%
“…The cyanobacterium Arthrospira platensis is an outstanding sunlight-driven cell factory that has the ability to convert carbon dioxide into high added value metabolites (Singh et al, 2017). This photosynthetic cyanobacterium have received much attention for high value metabolites such as α-tocopherol, β-carotene, lutein and γ-linolenic acid (Esquivel-Hernández et al, 2016;Sosa-Hernández et al, 2019) and bioactive effects such as antiproliferative, antitumor, antifungal, antibacterial, antimalarial, antiviral, antimycotic, cytotoxicity, multi-drug resistance reversers and immunosuppressive agents (Dixit & Suseela, 2013;Ediriweera et al, 2017;Kumari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…platensis contains approximately 65% of proteins, 20% of carbohydrates, 7% of minerals and 5% of lipids, (Campanella et al, 1999). After extraction of the high value metabolites, the resulting residual biomass, containing polysaccharides, monosaccharides and proteins (Esquivel-Hernández et al, 2017), can be a suitable feedstock for production of ethanol and lactic acid that can be used as biofuels and raw material of biopolymers in the frame of biorefinery concept and circular economy (Esquivel-Hernández et al, 2016).…”
Section: Introductionmentioning
confidence: 99%